Analisis Dimensi Loyalitas Pelangan Berdasarkan Perspektif Islam - Mashuri Mashuri (Iqtishaduna: Jurnal Ilmiah Ekonomi Kita)
This research is descriptive qualitative, the data used in this research is sourced from secondary data which includes books and scientific articles that are relevant to the research. The results of the analysis conducted that the concept of customer loyalty is more interpreted by behaviour or attitude. One positive attitude of the customer can be demonstrated through loyalty to the company's products and recommending these products to other parties. While negative attitudes are shown through negative words to other parties and move by making purchases to other companies. Those who are categorized as loyal customers are those who are very satisfied with certain products so they have the enthusiasm to introduce to anyone they know. Customer loyalty from an Islamic perspective is loyalty that does not conflict with the Islamic paradigm concept. Loyalty according to the Islamic paradigm consists of an implementation of monotheism, implementation of knowledge and implementation of worship.